The Natuna Waters Conflict between Indonesia and Vietnam: How is it resolved in International Law? - Tyas, Annida Ayuning (Faculty of Law, Universitas Negeri Semarang, 2023)
The Natuna Waters Conflict between Indonesia and Vietnam epitomizes the intricate web of maritime disputes and geopolitical tensions in the South China Sea region. At its core, the conflict revolves around competing claims over the sovereignty and resource exploitation rights in the waters surrounding the Natuna Islands. Against the backdrop of historical assertions and contemporary contestations, this abstract scrutinizes the application of international law as a framework for resolving the Natuna Waters Conflict. Central to the dispute resolution process are the principles enshrined in the United Nations Convention on the Law of the Sea (UNCLOS), which delineates maritime zones, rights, and responsibilities among coastal states. Both Indonesia and Vietnam are parties to UNCLOS, underpinning the significance of its provisions in addressing their respective claims. However, interpretations of UNCLOS provisions, especially regarding exclusive economic zones (EEZs) and continental shelf boundaries, have been contentious points of divergence between the two nations. Efforts to resolve the Natuna Waters Conflict through legal avenues have involved diplomatic negotiations, arbitration, and adjudication mechanisms provided for under UNCLOS. Despite these mechanisms being available, challenges persist in reaching a comprehensive resolution due to geopolitical interests and power dynamics in the region. Moreover, the role of external actors and regional organizations, such as the Association of Southeast Asian Nations (ASEAN) and major powers like China and the United States, further complicates the dispute resolution landscape. In navigating these complexities, understanding the interplay between legal principles and geopolitical realities is crucial. This abstract seeks to provide insights into the potential pathways for resolving the Natuna Waters Conflict within the framework of international law. By examining historical precedents, legal interpretations, and ongoing diplomatic efforts, it sheds light on the challenges and opportunities for achieving a peaceful and equitable resolution to this longstanding maritime dispute.